Financial model of investments to fixed assets - Beniušytė, Erika; Zonienė, Aurelija (Buhalterinės apskaitos teorija ir praktika, 2014)
The analysis of the investments to fixed assets revealed that there is no common system in evaluation of investments to fixed assets. The financial model of investments to fixed assets is recommended. The model consists of these stages: 1) the need determination of investments in fixed assets; 2) financing sources selection of the investments in fixed assets; 3) the calculation of financial benefits of the investments in fixed assets; 4) risk identification of the investment in fixed assets; 5) decision making.